Exenatide once weekly: sustained improvement in glycemic control and cardiometabolic measures through 3 years - MacConell, Leigh (Dove Medical Press, 2013)
BACKGROUND: Type 2 diabetes mellitus is a progressive metabolic disease necessitating therapies with sustained efficacy and safety over time. Exenatide once weekly (ExQW), an extended-release formulation of the glucagon-like peptide-1 receptor agonist exenatide, has demonstrated improvements in glycemic and cardiometabolic measures from 30 weeks to 2 years of treatment. Here, the efficacy and safety of treatment with ExQW for 3 years are described. METHODS: Patients were initially randomized to receive either ExQW (2 mg) or exenatide twice daily for 30 weeks. Following the initial 30 weeks, all patients were treated with ExQW in an open-label extension. Analyses of primary glycemic endpoints, beta-cell function, and cardiometabolic measures were assessed for patients who completed 3 years of ExQW treatment and for the intention-to-treat population. Safety and tolerability analyses were provided for the intention-to-treat population. RESULTS: Sixty-six percent of the intention-to-treat population (n = 295) completed 3 years of treatment (n = 194). At 3 years, a significant reduction in hemoglobin A(1c) (least squares mean ± standard error) of −1.6% ± 0.08% was observed, with 55% and 33% of patients achieving hemoglobin A(1c) targets of <7% and ≤6.5%, respectively. Consistent with a sustained reduction in hemoglobin A(1c), improvements in beta-cell function were also observed. Body weight was significantly reduced by −2.3 ± 0.6 kg. Reductions in blood pressure, total cholesterol, low-density lipoprotein cholesterol, and triglycerides were also observed. Adverse events reported most frequently during both controlled and uncontrolled periods included diarrhea, nausea, and vomiting of mostly mild intensity. The incidence of these adverse events decreased over time. Incidence of minor hypoglycemia was low and no major hypoglycemia was observed. CONCLUSION: ExQW produced clinically meaningful improvements in glycemic control that were durable through 3 years of treatment. Significant improvements in cardiometabolic measurements were also observed. ExQW was well-tolerated during long-term treatment and no new adverse events were noted. TRIAL REGISTRATION: ClinicalTrials.gov NCT00308139.